Предмет: Алгебра,
автор: Olgaefimova2002
Помогите решить ,срочно ❤️
Номера :154,165,170,180,185,193,197
Приложения:
Ответы
Автор ответа:
0
task/26488293
--------------------
154.
(x+3)⁴ - 3(x+3)² +2 =0 ;
замена : t =(x+3)²
t² -3t +2 =0 ⇔[ t = 1 ; t =2 .⇔[ (x+3)² =1 ; (x+3)² =2.⇔ [ x+3 =±1 ;x+3 =±√2 .
x₁= - 3 -√2 ; x₂= - 4 ; x₃ = -2 ; x₄ = - 3 +√2 .
165.
5/(x +1)² - 4 / (x+1) =1;
замена : t =1/ (x+1)
5t² - 4t -1 = 0 ;
t₁= (2 -3)/5 = -1/5 ⇒ 1/ (x₁+1) = - 1/ 5 ⇔ x₁ = - 6 ;
t₂=(2+3) /5 =1. ⇒ 1/ (x₂+1) =1 ⇔ x₂ = 0 .
170.
x + 3√x- 4 =0 ;
замена : t =√x ≥0
t² +3t - 4 =0 ;
t₁= (-3 -5)/2 = - 4 < 0 посторонний ;
t₂=(-3+5) /2 = 1. ⇒ √x =1 ⇔ x = 1 .
180. хорошо, что хорошо не видно...
3(x-2) - 16/(x-3) = 1 ;
3(x-3) - 16 /(x -3 ) + 2 =0 ;
замена : t =x - 3 ≠ 0 ⇔ x ≠ 3 .
3t² +2t - 16 =0 ;
t₁= (-1 - 7)/3 = - 8/3 ⇒ x₁ - 3 = - 8/3 ⇔ x₁ =1/3 ;
t₂=(-1+7) /3 = 2 . ⇒ x₂ - 3 = 2 ⇔ x₂ =5.
185.
1/( x-3) + 1/x =1/2; ОДЗ : x≠0 ; x ≠3 .
2(x +x -3) =x(x-3) ;
x² -7x +6 =0 ;
x₁=1 ;
x₂=6.
193.
(x ² -1)/ x =x² -1/x ; ОДЗ : x≠0 .
x -1/x = x² -1/x ;
x =x ² ;
x(x-1)= 0
x₁=0 → посторонний корень ;
x₂=1.
195.
(x² -2x -5) /(x-3)(x-1) +1/(x-3) =1 ; ОДЗ : x≠1 ; x ≠ 3 .
x² -2x -5 +x -1= (x-3)(x-1) ;
x² -2x -5 +x -1= x²- 4x + 3 ;
3x = 9 ;
x =3 ∈ ОДЗ → посторонний корень ;
x ∈ ∅
НА_КОНЕЦ
--------------------
154.
(x+3)⁴ - 3(x+3)² +2 =0 ;
замена : t =(x+3)²
t² -3t +2 =0 ⇔[ t = 1 ; t =2 .⇔[ (x+3)² =1 ; (x+3)² =2.⇔ [ x+3 =±1 ;x+3 =±√2 .
x₁= - 3 -√2 ; x₂= - 4 ; x₃ = -2 ; x₄ = - 3 +√2 .
165.
5/(x +1)² - 4 / (x+1) =1;
замена : t =1/ (x+1)
5t² - 4t -1 = 0 ;
t₁= (2 -3)/5 = -1/5 ⇒ 1/ (x₁+1) = - 1/ 5 ⇔ x₁ = - 6 ;
t₂=(2+3) /5 =1. ⇒ 1/ (x₂+1) =1 ⇔ x₂ = 0 .
170.
x + 3√x- 4 =0 ;
замена : t =√x ≥0
t² +3t - 4 =0 ;
t₁= (-3 -5)/2 = - 4 < 0 посторонний ;
t₂=(-3+5) /2 = 1. ⇒ √x =1 ⇔ x = 1 .
180. хорошо, что хорошо не видно...
3(x-2) - 16/(x-3) = 1 ;
3(x-3) - 16 /(x -3 ) + 2 =0 ;
замена : t =x - 3 ≠ 0 ⇔ x ≠ 3 .
3t² +2t - 16 =0 ;
t₁= (-1 - 7)/3 = - 8/3 ⇒ x₁ - 3 = - 8/3 ⇔ x₁ =1/3 ;
t₂=(-1+7) /3 = 2 . ⇒ x₂ - 3 = 2 ⇔ x₂ =5.
185.
1/( x-3) + 1/x =1/2; ОДЗ : x≠0 ; x ≠3 .
2(x +x -3) =x(x-3) ;
x² -7x +6 =0 ;
x₁=1 ;
x₂=6.
193.
(x ² -1)/ x =x² -1/x ; ОДЗ : x≠0 .
x -1/x = x² -1/x ;
x =x ² ;
x(x-1)= 0
x₁=0 → посторонний корень ;
x₂=1.
195.
(x² -2x -5) /(x-3)(x-1) +1/(x-3) =1 ; ОДЗ : x≠1 ; x ≠ 3 .
x² -2x -5 +x -1= (x-3)(x-1) ;
x² -2x -5 +x -1= x²- 4x + 3 ;
3x = 9 ;
x =3 ∈ ОДЗ → посторонний корень ;
x ∈ ∅
НА_КОНЕЦ
Похожие вопросы
Предмет: Алгебра,
автор: Аноним
Предмет: Математика,
автор: ksucha1981com
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Vika20040406